Web-Based Library Information System Using ReactJS: Case Study at the Faculty of Mathematics and Natural Sciences, Sam Ratulangi University - Freya Emily Theresia Tombokan; Benny Pinontoan; Mahardika Inra Takaendengan; Gifriend Yedija Talumingan (Jurnal Teknoinfo, 2026)
Digital transformation has reshaped the library landscape, transitioning from manual to digital systems. This research aims to develop a web-based library information system for the Faculty of Mathematics and Natural Sciences (FMIPA) at Sam Ratulangi University (UNSRAT) using ReactJS, NestJS, and PostgreSQL. The system is designed to address the inefficiencies of manual library management and enhance book information accessibility. The Rapid Application Development (RAD) method was applied, encompassing requirements planning, user design, construction, and cutover. Data were collected through interviews, observations, and surveys. The results demonstrate that the system facilitates online book searching and borrowing, accelerates administrative processes, and improves service efficiency. User satisfaction evaluation through surveys showed high levels of approval. This system is expected to support teaching and learning processes and enhance the quality of library services at FMIPA UNSRAT.